Some deviations of form: a little essay on psychoanalysis, art and aesthetics - Dionisio, Gustavo Henrique [UNESP] (Scientific Research Publishing, 2014)
This work intends to investigate the use of psychoanalytical theory within the aesthetic and critical contemporary art field. To this purpose, it focuses on two philosophers who have become significant in our time: the art critic Hal Foster and the art historian Georges Didi-Huberman. This study aims to show how far the concepts generated in psychoanalytic praxis allowed interpretations that disrupt the traditional aesthetics field. This type of analysis is possible once we abandon the paradigm of “applied psychoanalysis”, which is still current in non-clinical setting. Finally, the proposal wants to argue that the category of the amorphous may clarify certain aesthetic experiences that range from the modernity of art through postmodernity.
Keywords: Psychoanalysis; Aesthetics; Figurability; Deferred Action; Amorphous